Project Based Learning with Stem Approach to Alternative Energy Material as Effective Learning to Improve Problem Solving Skills - Roslina, Roslina; Liliawati, Winny; Hasanah, Lilik (Phenomenon : Jurnal Pendidikan MIPA, 2023)
This study aims to determine the effectiveness of STEM-PjBL learning in improving students' problem-solving abilities in alternative energy materials. This research was conducted in one of the high schools in the city of Bandung. Samples were obtained by rational sampling of 35 students in class X MIPA I (experimental class) and 35 students in class X MIPA II (control class). The method used is a quasi-experimental design with a non-equivalent control group design. Data collection technique is a description test in the form of pre-test and post-test. Based on data analysis it is known that the use of STEM-PjBL can improve students' problem solving skills (N-Gain = 0.65) in the experimental class compared to the control class (N)-Gain = 0.44). The t-test results with SPSS 22 with Sig. (2-value) less than 0.05 indicates that there is a significant difference in the increase in the problem solving ability of students in the experimental class and the control class. Based on these results, learning has a positive impact on students' problem solving abilities. STEM-PjBL learning can be used as an alternative teaching strategy at various school levels.